ORNAC Standards Under Review - Hay, Vija (Operating Room Nurses Association of Canada Journal, 1995)
In this issue of the Journal there is an article by one of the many excellent speakers at the May, 1995 ORNAC National Conference in Vancouver. The author expresses concern for the operating room nurse as she lists the numerous and potentially dangerous contents of surgical smoke. Just how serious is the effect of surgical smoke, are we required to evacuate surgical smoke, and do we in fact take measures to evacuate smoke? To find answers to practice issues such as these, we look for guidance in ORNAC's Recommended Clinical Practice Standards for Perioperative Nursing.